The need and demand for renal replacement therapy in ethnic minorities in England. Issue 3 (June 1996) - Roderick, P J; Raleigh, V S; Hallam, L; Mallick, N P
Abstract : STUDY OBJECTIVE: The study aimed to determine the relative risk of being accepted for renal replacement treatment of black and Asian populations compared with whites in relation to age, sex, and underlying cause. The implications for population need for renal replacement therapy in these populations and for the development of renal services were also considered. DESIGN/SETTING: This was a cross sectional retrospective survey of all patients accepted for renal replacement treatment in renal units in England in 1991 and 1992. PATIENTS: These comprised all 5901 patients resident in England with end-stage renal failure who had been accepted for renal replacement therapy in renal units in England and whose ethnic category was available from the units. Patients were categorised as white, Asian, black, or other. Population denominators for the ethnic populations were taken from the 1991 census. The census categories Indian, Pakistani, and Bangladeshi were aggregated to form the denominator for Asian patients, and black Caribbeans, black Africans, and black others were aggregated to form the denominator for black patients. MAIN RESULT: Altogether 7.7% of patients accepted were Asian and 4.7% were black; crude relative acceptance rates compared with whites were 3.5 and 3.2 respectively. Age sex specific relative acceptance ratios increased with age in both ethnic populations and were greater in females. Age standardised acceptance ratios were increased 4.2 and 3.7 times in Asian and black people respectively. The most common underlaying cause in both these populations was diabetes; relative rates of acceptance for diabetic end-stage renal failure were 5.8 and 6.5 respectively. The European Dialysis and Transplant Association coding system was inaccurate for disaggregating non-insulin and insulin dependent forms. "Unknown causes" were an important category in Asians with a relative acceptance of rate 5.7. The relative rates were reduced only slightly when the comparison was confined to the district health authorities with large ethnic minority populations, suggesting that geographical access was not a major factor in the high rates for ethnic minorities. CONCLUSION: Acceptance rates for renal replacement treatment are increased significantly in Asian and black populations. Although data inaccuracies and access factors may contribute to these findings, the main reason is probably the higher incidence of end-stage renal failure. This in turn is due to the greater prevalence of underlying diseases such as non-insulin dependent diabetes but possibly also increased susceptibility of developing nethropathy. The main implication is that these populations age demand for renal replacement treatment will increase. This will have an impact nationally but will be particularly apparent in areas with large ethnic minority populations. Future planning must take these factors into account and should include strategies for preventing chronic renal failure, especially that due to non-insulin dependent diabetes and hypertension. The data could not determine the extent to which population need was being met; further studies are required to estimate the incidence of end-stage renal failure in ethnic minority populations.